Mexican Emigration to the United States, 1897-1931 - Cardoso, Lawrence A. (University of Arizona Press, 1980)
Rapid change in the land and labor system in rural Mexico during the 1890s destroyed the ancestral homes of the peasantry, forcing them either onto privately owned haciendas or into the migratory labor stream. The anarchy, inflation, and fear for personal safety that resulted from the Mexican Revolution of the 1910 provided a further impetus to migratory patterns that otherwise might not have emerged, considering the people's strong ties to their ancestral land. During the same era, capitalist modernization in the United States was creating a strong demand for low-paid, unskilled labor, especially for agricultural and railroad work. Mexico's newly created class of migrant workers rushed across the border to fill this demand, setting in motion a social, economic, and political phenomenon that Lawrence Cardoso analyzed here in detail. What set this study apart, however, is the author's focus on the ' Human element," as revealed through the Mexican workers' hopes, fears, and reactions to events of their time.